3D simulation of arc envelope grinding of non-axisymmetric aspheric surface. (7th March 2007) - Xie, J.; Xu, W.W.; Tamaki, J.
A new simulation method for envelope grinding of non-axisymmetric aspheric surface was proposed by using 3D virtual curve grinding without complex mathematical calculations. The aim is to verify 3D distribution of envelop traces and form errors on ground curve surface. First, 3D objects of arc-shaped grinding wheel and workpiece were established in AutoCAD, then Boolean operation was conducted to simulate form grinding by AutoLISP program, finally tool path number and form errors were analysed. Grinding experiments proved the validity of this simulation method. It was shown that 3D envelope traces and form errors distribution can be displayed by simulation for tool path planning and form error compensation. It was confirmed that equal-envelope-height grinding can greatly reduce tool paths when precision grinding of very large curvature is conducted. In addition, form accuracy PV only increases 4.17 µm in the range of 200 × 20 mm² for wheel radial wear of 1 mm.